The Presence of Investor Overconfidence in the Stock Market and Its Impact on Investment Decisions in South Africa - Nyasha, Jameson; Muguto, Lorraine; Singh, Akshil; Govender, Caitlyn; Thakur, Mikaela; Chetty, Trevisha; Chetty, Trishana; Muzindutsi, Paul-Francois (Acta Universitatis Danubius. Œconomica, 2025)
Investor overconfidence continues to generate high interest due to its perceived impact on investment decisions. This research investigated the existence of overconfidence among investors in South Africa and its link to investor decision making and socio-demographic variables in South Africa. A quantitative approach with a structured survey questionnaire was used to collect data from 107 professional investors. The analysis was conducted using descriptive statistics, ANOVA, correlations and regression analysis. Overall, the findings suggest that investor overconfidence is present among South African investors and significantly impacts investor decision making. The results further indicate that demographic variables have a significant influence on investor overconfidence and decision making, where young, more inexperienced investors and males tend to be more overconfident in their investment decisions. This study has important implications for investors and policymakers regarding investor overconfidence in decision making.